Usborne Farmyard Tales : Pig Gets Lost - Heather Amery (America Usborne Publishing, 2004)
This is one of a series of stories featuring Poppy and Sam, their dog Rusty, Curly the pig and Woolly the sheep, as they go about their lives on Apple Tree Farm.
Keywords: Independent Reading -- Independent Reading